2019
DOI: 10.1177/2158244019865772
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service Teachers’ Attitudes Toward Inclusive Education During Their Studies in Bahrain Teachers College

Abstract: This study explored pre-service teachers’ attitudes toward inclusive education. The Sentiments, Attitudes, and Concerns about Inclusive Education–Revised (SACIE-R) scale was completed by 138 teacher candidates in a teacher preparation program in Bahrain Teachers College. The findings revealed that candidate teachers needed more opportunities to interact with and teach children with disabilities during their school practicum; they also needed more preparation and knowledge about the educational policies related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 22 publications
2
24
0
3
Order By: Relevance
“…Other studies have also criticised the knowledge base of teachers at various levels. For instance, a report by AlMahdi and Bukamal (2019) showed that 17.4% of the candidate teachers from the Bay District in the Philippines had poor knowledge about an inclusive policy, while others demonstrated a moderate understanding of the concept. Earlier studies (Pottas, 2005; C. R. Dapudong, 2014;Wanjiru, 2017) have also reported that many potential teachers exhibit partial knowledge of inclusive education as an educational philosophy that can conveniently accommodate all learners, irrespective of their diverse learning needs or location.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other studies have also criticised the knowledge base of teachers at various levels. For instance, a report by AlMahdi and Bukamal (2019) showed that 17.4% of the candidate teachers from the Bay District in the Philippines had poor knowledge about an inclusive policy, while others demonstrated a moderate understanding of the concept. Earlier studies (Pottas, 2005; C. R. Dapudong, 2014;Wanjiru, 2017) have also reported that many potential teachers exhibit partial knowledge of inclusive education as an educational philosophy that can conveniently accommodate all learners, irrespective of their diverse learning needs or location.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the light of the arguments in the literature, it is possible to say that teachers' beliefs and attitudes play a crucial role in the implementation and success of inclusive education. There are many studies (AlMahdi & Bukamal, 2019;Alnahdi, Saloviita, & Elhadi, 2019;Altun & Filiz, 2020;Anılan & Kayacan, 2015;Deniz & Çoban, 2019;Güleryüz & Özdemir, 2015;Katıtaş & Coşkun, 2020;Kurt & Tomul, 2020 ;Magumise & Sefotho, 2020;Moberg, Muta, Korenaga, Kuorelahti, & Savolainen, 2020;Özcan, 2020;Page, Boyle, McKay, & Mavropoulou, 2019;Saloviita, 2020;Sheehy, Budiyanto, Kaye, & Rofiah, 2019;Vanderpuye, Obosu, & Nishimuko, 2020;Woodcock & Woolfson, 2019;You, Kim, & Shin, 2019) in the literature that investigated teachers' attitudes, beliefs and competencies towards inclusive education. However, it was seen that there was a scant of studies (Kök, Balcı, & Bilgiz, 2017;Krischler & Pit-ten Cate, 2019) with the teachers who were actively provide inclusive education, that is having at least one special needs student in their class.…”
Section: Issn-2199-353xmentioning
confidence: 99%
“…Los sentimientos que expresan los docentes hacia los estudiantes que presentan alguna discapacidad suelen encontrarse orientadas hacia la compasión, especialmente entre los que se encuentran en etapa de formación [11]. En docentes de etapa preescolar también se han encontrado valores positivos para esta dimensión, sin embargo, no suelen ser suficientes para determinar una actitud firme hacia la implementación de políticas inclusivas cuando va acompañada de preocupaciones, las Diaz, Rivera & Vega.…”
Section: Introductionunclassified
“…Las actitudes en los docentes suelen ser positivas hacia la inclusión, sin embargo, se han reportado actitudes de aprensión cuando se trata de niños que se comportan de manera agresiva en el aula o requieren de tecnologías comunicativas en las clases regulares [11]. Esta actitud no varía necesariamente como resultado de la experiencia que tenga el docente atendiendo casos de niños con necesidades educativas especiales, especialmente cuando se trata de docentes que no han recibido una capacitación previa en educación inclusiva.…”
Section: Introductionunclassified